Measuring Group Dynamics Index (GDI) of Beef Cattle Farmers in West Lombok Regency, West Nusa Tenggara - Taqiuddin, Moh.; Media, I Gusti Lanang; Nachida, Maya; Hermansyah, Hermansyah; Fachry, Anwar; Nugroho, Muh. Prasetyo; Putra, Ryan Aryadin; Villano, Renato Andrin (Buletin Peternakan, 2025)
This study examines the social dynamics of cattle farmer groups as a strategic approach to supporting the sustainability of cattle farming in rural areas. There is evidence to suggest that social dynamics play an important role in livestock farming, impacting productivity, efficiency and sustainability. The main objective of this study was to develop a Group Dynamics Index (GDI) with a specific focus on evaluating eight key elements of group dynamics: purpose, structure, task function, coaching, cohesiveness, atmosphere, pressure, and group effectiveness. The study employed a quantitative descriptive survey methodology, involving 150 respondents drawn from three sub districts in West Lombok Regency. Data collection was conducted using a structured Likert scale-based questionnaire, which facilitated the measurement of respondent’s perceptions and attitudes. A weighted analysis approach was applied to the gathered data to generate a cumulative index. The findings indicate that structural factors, such as decision-making and task division, and non-structural elements, including interpersonal relationships and social support, significantly influence group dynamics. It was observed that farmer groups in the Lembar sub-district demonstrated the highest cumulative index (0.68), exhibiting excellence in aspects such as group structure and task function. Farmer groups in the Narmada sub-district exhibited a cumulative index of 0.65, distinguishing themselves through their notable group cohesiveness and atmosphere. Conversely, the farmer group in Gunung Sari demonstrated strong member loyalty (0.60) yet exhibited a need for substantial enhancement in internal management, particularly concerning task function and group pressure. The study concludes that the sustainability and effectiveness of group dynamics are contingent on the balanced integration of structural and non structural elements. A comprehensive, holistic approach that harmonizes internal management and social relations is essential to support overall group performance. The GDI proved to be a relevant and applicable tool for comprehensively evaluating group dynamics